Cover Image. Issue 11 (31st October 2020) - DunnGalvin, Audrey; Gallop, Katy; Acaster, Sarah; Timmermans, Frans; Regent, Lynne; Schnadt, Sabine; Podestà, Marcia; Sánchez, Angel; Ryan, Robert; Couratier, Pascale; Feeney, Mary; Hjorth, Betina; et al.
Abstract : The cover image is based on the Original Article‐Clinical Allergy APPEAL‐2: A pan‐European qualitative study to explore the burden of peanut‐allergic children, teenagers and their caregivers by Audrey DunnGalvin et al., https://doi.org/10.1111/cea.13719 .